Hybrid Optimized LMMSE based Channel Estimation with Low Power Trellis Coded Modulation - Neeta Nitin Thune; Senthil Kumaran V N; Ramakrishna Guttula; Rajakumar B R; GONDHI NAVABHARAT REDDY; Binu D (International Journal of Engineering Education, 2021)
In the wireless channel environment, the data transmission faces many safety problems and power transmission loss. This results with the negative impacts while precise channel estimation. Furthermore, the existing channel estimation (CE) model directly estimates the channel matrix; still, the accuracy and the high complexity may cause path loss. Alternate to the direct estimation in the channel matrix, the parameter estimation model is used to solve the above issues. Moreover, the training based CE including Linear Minimum Mean Square Error (LMMSE) and Least Square Error (LSE) are ubiquitous in certain wireless standards to reduce the Mean Square Error (MSE) among the estimated and original channel. Certain intelligent optimized techniques are introduced to optimize the channel. This paper intends to introduce a Trellis Coded Modulation (TCM) with hybrid optimization in LMMSE for the Optimal CE. Moth amalgamated Elephant Herding Optimization (MAEHO) algorithm is the proposed hybrid optimization. At last, the performance of the adopted model is computed over other existing schemes in terms of various measures.